Complete plastid genome of Cumathamnion serrulatum (Ceramiales, Rhodophyta). Issue 7 (3rd July 2021) - Kim, Hocheol; Lee, Do-Yun; Seo, Chang Wan; Cho, Chung Hyun; Yoon, Hwan Su
Abstract: We report the complete plastid genome of Cumathamnion serrulatum, also known as Delesseria serrulata . The plastid genome was 174, 192 bp in size. Annotation showed there were 193 protein coding genes, three ribosomal RNAs, and 29 transfer RNAs. One intron was found, and the GC content was 27.2%. The maximum likelihood tree with the concatenated 177 plastid coding genes showed a strong monophyletic relationship to Membranoptera spp. within the Ceramiales.